0218 A Pilot Of A Simulation Scenario Scripting Workshop For Medical Students: Exposing Students To Teaching And Learning Using Simulation-based Medical Education. (1st November 2014) - Gopal, Alan; Purva, Makani
Abstract : Background and context: Teaching is recognised as an important part of clinical governance and is a skill taught at every stage of the medical career. 1 The Hull Institute of Learning and Simulation (HILS), 2 a primarily postgraduate institute, runs a Student-Selected Component (SSC) 3 for undergraduate medical students in early clinical years at Hull York Medical School. 4 This SSC trains students how to use simulation to deliver medical education. 5 Methodology: An innovative partnership of a final year medical student (who had previously completed the SSC) paired with direct senior supervision enabled design insight from both sides of the teaching partnership. 6 The workshop was adapted from the highly successful postgraduate HILS Train the Trainers course 2 to suit an audience at a much younger career stage. This bespoke workshop package combines an interactive plenary with a practical demonstration of what a simulation scenario entails for the both the learner and instructor. This was followed by facilitating a friendly competitive peer-assisted learning task; students were divided into teams and designed a short scenario for their opposition; allowing them time as both delegates and instructors. Pre and post-course questionnaires were utilised to assess educational value of the session. Outcomes: Students demonstrated statistically and educationally significant increases in scores for confidence in designing (scale 1(not confident) to 7(confident); increase of 2.4/7, p = 0.01) and delivering their own simulated scenario (increase of 1.6/7, P = 0.04). Overwhelmingly the session was rated enjoyable, useful and suitable for their requirements quantitatively and qualitatively. Impact: At the learner level, the dramatic improvement in scores between pre and post-course questionnaires gives strong support for the intended integration of this workshop as part of the SSC core programme. This pilot demonstrated the strength of staff-student professional partnerships 6 in delivery of medical education, encouraging further efforts to optimise this internally highly rated SSC in striving for excellence. References: General Medical Council. (GMC). (2006). Good Medical Practice 2013. London, GMC The Hull Institute of Learning and Simulation (HILS). Courses [Internet]. [cited 2014 Sept 1]. Available: http://www.hey.nhs.uk/hils/courses.htm/ NHS Medical Careers. Student-Selected Components [Internet]. [cited 2014 Sept]. Available: https://www.medicalcareers.nhs.uk/medical_students/student-selected_components.aspx Hull York Medical School (HYMS). Scholarship and Special Interest Programmes [Internet]. [cited 2014 Sept]. Available: http://www.hyms.ac.uk/undergraduate/medicine-at-hyms/scholarshipandspecialinterestprogrammes/ Swamy M, Bloomfield TC et al . Role of SimMan in teaching clinical skills to preclinical medical students. BMC Med Educ 2013;13:20 Klazina Visser Katinka JAH, Prince Albert JJA et al . Student participation in educational management and organization. Medical Teacher 1998;20(5):451–454